Social-Economic Factor as a Determining Factor of Parameters of use and Performance in a TLVE Applied to Anatomy Teaching (Global Journal of Human-Social Science, 2014)
Abstract not found
Keywords: anatomy teaching social-economic factor teaching and learning virtual space